2013
DOI: 10.1016/j.drugalcdep.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Emerging adults’ treatment outcomes in relation to 12-step mutual-help attendance and active involvement

Abstract: Background Participation in Alcoholics Anonymous (AA) and Narcotics Anonymous (NA) during and following treatment has been found to confer recovery-related benefit among adults and adolescents, but little is known about emerging adults (18–24yrs). This transitional life-stage is distinctive for greater distress, higher density of psychopathology, and poorer treatment and continuing care compliance. Greater knowledge would inform the utility of treatment referrals to 12-step organizations for this age-group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 52 publications
2
72
0
Order By: Relevance
“…Given the overwhelming evidence that addiction is a chronic relapsing condition (McLellan, Lewis, O'Brien, & Kleber, 2000), an abstinence-only approach is not responsive to the needs of all people with AOD problems. Though there is evidence to support the effectiveness of this approach to helping people increase abstinence and reduce drinking-related problems (Kelly, Stout, & Slaymaker, 2013;Magura, Cleland, & Tonigan, 2013), a core principle which the US research-based guide to principles of drug addiction treatment (National Institute on Drug Abuse [NIDA], 2012) stresses is that no single treatment is appropriate for all. Thus, it is imperative to investigate whether a broader philosophical perspective on substance use might enable us to modify negative attitudes to bolster the effectiveness of SW practice.…”
Section: Harm Reductionmentioning
confidence: 99%
“…Given the overwhelming evidence that addiction is a chronic relapsing condition (McLellan, Lewis, O'Brien, & Kleber, 2000), an abstinence-only approach is not responsive to the needs of all people with AOD problems. Though there is evidence to support the effectiveness of this approach to helping people increase abstinence and reduce drinking-related problems (Kelly, Stout, & Slaymaker, 2013;Magura, Cleland, & Tonigan, 2013), a core principle which the US research-based guide to principles of drug addiction treatment (National Institute on Drug Abuse [NIDA], 2012) stresses is that no single treatment is appropriate for all. Thus, it is imperative to investigate whether a broader philosophical perspective on substance use might enable us to modify negative attitudes to bolster the effectiveness of SW practice.…”
Section: Harm Reductionmentioning
confidence: 99%
“…Finally, Kelly, Stout, and Slaymaker (2013) found that in a sample of 303 'emerging adults' (aged between 18-24) the greatest predictor of alcohol abstinence was active involvement at AA in the form of active verbal participation during meetings (F = 7.85; p < 0.002) and considering oneself a member of the group (f = 9.17; p < 0.005). Furthermore, Kelly et al (2013) found that meeting with others outside the group (F = 6.58 p < 0.01) and working the twelve steps (F = 5.40; p < 0.02) were the greatest predictors of reduced heavy days drinking.…”
Section: Involvementmentioning
confidence: 94%
“…Motivational enhancement, cognitive-behavioral and family-based therapeutic approaches were used to facilitate problem recognition, treatment engagement, and recovery. Participants remained in treatment for an average of 25.5±5.7 days (range 4–35 days) and 83.9% were discharged with staff approval (Kelly et al, 2013), indicating a high rate of treatment completion. Opioid detoxification was conducted primarily with buprenorphine.…”
Section: Methodsmentioning
confidence: 99%
“…Residential programs generally offer the potential for opioid detoxification, coping skills development, and facilitated involvement in the 12-step recovery community (Borkman et al,, 2007; Kelly et al, 2013). Relapse is very common among the opioid-dependent after abstinence-based inpatient treatment, leading to a perceived lack of efficacy of residential treatment (Smyth et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation